Basic psychological needs, more than mindfulness and resilience, relate to medical student stress: A case for shifting the focus of wellness curricula. (1st December 2020) - Neufeld, Adam; Mossière, Annik; Malin, Greg
Abstract: Purpose: Medical student distress is an increasing concern in medical education. Addressing this issue requires a comprehensive understanding of what factors influence learners' stress in medical school. Grounded in Self-Determination Theory (SDT), this study explores the relative association between medical students' mindfulness, resilience, basic psychological needs, and perceived stress. Materials and methods: Of all year 1–4 medical students at our institution, 197 (49%) completed an online survey, measuring satisfaction and frustration of their basic psychological needs (autonomy, competence, relatedness), mindfulness, resilience, and perceived stress. Variables were assessed in relation to perceived stress, controlling for students' gender and year. Results: Higher mindfulness, resilience, and need satisfaction were associated with lower perceived stress. Conversely, need frustration was associated with higher perceived stress. When students' need frustration was included in the model, the association between mindfulness, resilience, and perceived stress weakened. Third years reported more autonomy frustration than all other years. Compared to males, females in second and fourth year reported higher stress, lower mindfulness and resilience, and less competence fulfilment. Conclusions: Findings of this study suggest that, while mindfulness and resilience are important qualities for medical student well-being, their stress-protective benefits may diminish when students' basic psychological needs are frustrated in medical school. Addressing potentially need-thwarting aspects of the learning environment is therefore recommended, to help reduce student stress and promote their well-being. Preliminary suggestions on how this might be achieved are discussed, from an SDT perspective.